2022
DOI: 10.3389/fpls.2022.851538
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Early Blight Resistance in Tetraploid Potato

Abstract: Early blight, caused by the fungus Alternaria solani, is one of the most economically important diseases of potatoes worldwide. We previously identified a tetraploid potato clone, B0692-4, which is resistant to early blight. To dissect the genetic basis of early blight resistance in this clone, a full-sib tetraploid potato population including 241 progenies was derived from a cross between B0692-4 and a susceptible cultivar, Harley Blackwell, in this study. The population was evaluated for foliage resistance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The fungicides in use are becoming less potent due to mutations in the active sites and fungicide-resistant populations of A. solani, which have been reported in multiple countries [8][9][10][11][12]. In addition, excess or prolonged application of fungicides may lead to the accumulation of these chemicals in the soil and water sources, which may become environmental contamination and food safety problems [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The fungicides in use are becoming less potent due to mutations in the active sites and fungicide-resistant populations of A. solani, which have been reported in multiple countries [8][9][10][11][12]. In addition, excess or prolonged application of fungicides may lead to the accumulation of these chemicals in the soil and water sources, which may become environmental contamination and food safety problems [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The resistance is suggested to be polygenic and thus quantitative in nature. It is also linked to the foliage maturity of potato cultivars [19,20,15]. It has been shown that potato cultivars maturing late are more resistant to early blight and vice versa [15,16,17,21,20].…”
Section: Introductionmentioning
confidence: 99%
“…The fungicides in use are becoming less potent due to mutations in the active sites and fungicide-resistant populations of A. solani, which have been reported in multiple countries [8,9,10,11,12]. In addition, excess or prolonged application of fungicides may lead to the accumulation of these chemicals in the soil and water sources, which may become environmental contamination and food safety problems [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations